Citrate as Cost-Efficient NADPH Regenerating Agent - Oeggl, Reinhard; Neumann, Timo; Gätgens, Jochem; Romano, Diego; Noack, Stephan; Rother, Dörte (Frontiers in Bioengineering and Biotechnology, 2018)
The economically efficient utilization of NADPH or NADH-dependent enzymes requires the regeneration of consumed reduction equivalents. This cofactor regeneration is classically done via an additional substrate, and if necessary enzyme. We now demonstrate an easy-to-apply cofactor regeneration approach, which can especially be used in screening applications. Simply by applying citrate to a buffer or directly using citrate/-phosphate buffer NADPH can be regenerated by native enzymes of the TCA cycle, practically present in all aerobic living organisms. Apart from viable-culturable cells, this regeneration approach can also be applied with lyophilized cells and even crude cell extracts. This is exemplarily shown for the synthesis of 1 phenylethanol from acetophenone with several oxidoreductases. The mechanism of NADPH regeneration by TCA cycle enzymes was further investigated by a transient isotopic labeling experiment feeding [1,5-13C]citrate. This revealed that the regeneration mechanism can further be optimized by genetic modification of two competing internal citrate metabolization pathways, the glyoxylate shunt and the glutamate dehydrogenase.